2017
DOI: 10.1097/hp.0000000000000670
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Risk of Cardiovascular Diseases in the Cohort of Russian Emergency Workers of the Chernobyl Accident

Abstract: This paper continues a series of publications that analyze the impact of radiation on incidence of circulatory system diseases in the cohort of Russian recovery operation workers (liquidators) and presents the results of the analysis of cardiovascular disease (CVD) incidence. The studied cohort consists of 53,772 liquidators who arrived in the Chernobyl accident zone within the first year after the accident (26 April 1986 to 26 April 1987). The individual doses varied from 0.0001 Gy to 1.42 Gy, and the mean ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 11 publications
1
33
0
Order By: Relevance
“…The current study adds to the evidence relating to the risk of CD and low-level exposure to radiation, recently reviewed by Azizova, et al (17,23) and Little (16). The pattern of results from studies of CD after low or moderate acute doses and protracted exposures at low dose rates does not point to an obvious explanation, causal or otherwise, for the reported associations (42)(43)(44)(45)(46)(47). Studies of CD in the Japanese atomic bomb survivors have produced results that do not invite a straightforward interpretation because of, inter alia, substantial variation of risks between disease subtypes (42)(43)(44).…”
Section: Comparison With Previous Studiessupporting
confidence: 52%
See 1 more Smart Citation
“…The current study adds to the evidence relating to the risk of CD and low-level exposure to radiation, recently reviewed by Azizova, et al (17,23) and Little (16). The pattern of results from studies of CD after low or moderate acute doses and protracted exposures at low dose rates does not point to an obvious explanation, causal or otherwise, for the reported associations (42)(43)(44)(45)(46)(47). Studies of CD in the Japanese atomic bomb survivors have produced results that do not invite a straightforward interpretation because of, inter alia, substantial variation of risks between disease subtypes (42)(43)(44).…”
Section: Comparison With Previous Studiessupporting
confidence: 52%
“…Studies of CD in the Japanese atomic bomb survivors have produced results that do not invite a straightforward interpretation because of, inter alia, substantial variation of risks between disease subtypes (42)(43)(44). Studies of Russian ''liquidators'' of the Chernobyl accident have reported raised risks of CD incidence with respect to external dose, but based on a surprisingly high proportion of cases among the liquidators (45,46). The authors of the recent INWORKS analysis of CD mortality among nuclear workers (including those from Sellafield), which showed significantly increased ERR/Sv external dose, warned that heterogeneity of risks did not permit firm conclusions to be drawn (47).…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…It has been recognized for many years that acutely delivered high doses of ionizing radiation can cause heart disease (1), including damage to the structure of the heart and arteries (2,3). At protracted exposures to low doses or low dose rates, there is also evidence of an excess circulatory disease risk, such as that found in studies of radiation workers (4)(5)(6)(7)(8)(9). However, while plausible, if not completely understood, mechanisms exist by which acute high doses can affect the circulatory system (10), for lowdose or low-dose-rate radiation exposures only tentative mechanisms have been proposed (11).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, therapeutic chest irradiation, which involves high-dose ionizing radiation, among patients with lymphoma or different solid tumor cancers, also increases the risk for cardiovascular diseases (16)(17)(18). Occupational exposures to radiation, which are generally at lower doses but over longer durations than atomic bomb and therapeutic radiation exposure, have been inconsistently associated with cardiovascular diseases (19)(20)(21)(22). Mining, processing, and transporting uranium ore, associated with occupational exposure to radiation, have been investigated as a risk factor for cardiovascular disease, but current literature is inconclusive, constituting a critical gap in this field (21,(23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%